Participação das coleções do Portal de Periódicos da Capes na produção científica dos pesquisadores da área de Direito no triênio 2010-2012: um estudo bibliométrico - Gomes, Eliane Azevedo (2017)
In this research the Capes Portal of Scientific Journals is seen as a public policy of access to information based on the concept of information policy defined by González de Gómez. It is inferred that the Capes Portal of Scientific Journals while policy is an action aimed to modify the current information system. It evaluates the participation of the foreign titles from the Capes Portal of Scientific Journals on the production of the Brazilian researchers from the area of Law according to the characteristics found in their scientific production during the triennium 2010-2012. It resorts to the study of scientific production focused on foreign scientific articles and on the analysis of the quotes for interpretation, treatment and analysis of the international scientific production from the permanent teachers’ staff of the post-graduation in Law Programs with master’s and doctorate that got grades 4, 5 and 6 on the triennium 2010-2012, as well as for comparison of the referred titles to the available on the Capes Portal of Scientific Journals. It compares the referred titles from the scientific journals to those available on the Capes Portal of Scientific Journals. It shows that the offer of titles by the Capes Portal of Scientific Journals for the area of Law has been diminishing along the analyzed period. It indicates that the researchers from the area of Law use very little of the titles available at the Portal, preferring to use titles that are available in open access and in printed format. Also it is perceived that titles of interest of the researchers that still aren’t part of the Capes Portal collection and deserve attention.